The gold-standard treatment for social anxiety disorder: A roadmap for the future - Chowdhury, Nayeefa; Khandoker, Ahsan H. (Frontiers in Psychology, 2023)
Exposure therapy (ET) which follows the Pavlovian extinction model is regarded as the gold-standard treatment for social anxiety disorder (SAD). The prospect of virtual reality in lieu of a traditional laboratory setting for the treatment of SAD has not been rigorously explored. This scoping review aimed to summarize, find gaps in the current literature, and formulate future research direction by identifying two broad research questions about the comparative efficacy between in vivo ET and virtual reality exposure therapy (VRET), and the effectiveness of the Pavlovian extinction model in treating SAD. The criteria for effectiveness were effect size, relapse prevention, attrition rate and ecological validity. A literature search on recent randomized controlled trials yielded a total of 6 original studies (N=358), excluding duplication and overlapping participants. All studies supported that VRET was as effective as in vivo ET. It was highlighted that behavioural therapy that follows classical conditioning principles has a high attrition and relapse rate. Comparisons were drawn between the efficacy of the Pavlovian extinction model and other existing models, including third wave approaches. It is suggested that the neural markers be included as efficacy measures in treating SAD. The gold-standard treatment for SAD requires a paradigm shift through rigorous longitudinal comparative studies.